4‐Nonylphenol induces disruption of spermatogenesis associated with oxidative stress‐related apoptosis by targeting p53‐Bcl‐2/Bax‐Fas/FasL signaling. Issue 3 (18th April 2016) - Duan, Peng; Hu, Chunhui; Butler, Holly J.; Quan, Chao; Chen, Wei; Huang, Wenting; Tang, Sha; Zhou, Wei; Yuan, Meng; Shi, Yuqin; Martin, Francis L.; Yang, Kedi
ABSTRACT: 4‐Nonylphenol (NP) is a ubiquitous environmental chemical with estrogenic activity. Our aim was to test the hypothesis that pubertal exposure to NP leads to testicular dysfunction. Herein, 24 7‐week‐old rats were randomly divided into four groups and treated with NP (0, 25, 50, or 100 mg/kg body weight every 2 days for 20 consecutive days) by intraperitoneal injection. Compared to untreated controls, the parameters of sperm activation rate, curvilinear velocity, average path velocity, and swimming velocity were significantly lower at doses of 100 mg/kg, while sperm morphological abnormalities were higher, indicating functional disruption and reduced fertilization potential. High exposure to NP (100 mg/kg) resulted in disordered arrangement of spermatoblasts and reduction of spermatocytes in seminiferous tubules, while tissues exhibited a marked decline in testicular fructose content and serum FSH, LH, and testosterone levels. Oxidative stress was induced by NP (50 or 100 mg/kg) as evidenced by elevated MDA, decreased SOD and GSH‐Px, and inhibited antioxidant gene expression ( CAT, GPx, SOD1, and CYP1B1 ). In addition, NP treatment decreased proportions of Ki‐67‐positive cells and increased apoptosis in a dose‐dependent manner. Rats treated with 100 mg/kg NP exhibited significantly increased mRNA expression of caspase‐1, ‐2, ‐9, and ‐11, decreased caspase‐8 and PCNA1 mRNA expression, downregulation of Bcl‐2/Bax ratios and upregulation of Fas, FasL, and p53 at the protein and mRNA levels. Taken together, NP‐induced apoptosis, hormonal deficiencies, and depletion of fructose potentially impairs spermatogenesis and sperm function. p53‐independent Fas/FasL‐Bax/Bcl‐2 pathways may be involved in NP‐induced oxidative stress‐related apoptosis. © 2016 Wiley Periodicals, Inc. Environ Toxicol 32: 739–753, 2017.